Examination of accessory extensor carpi radialis longus and brevis musculotendinous units for functional impact and tendon transfer suitability - Jay J. Byrd; Andrew C. White; Travis L. McCumber; Ethan L. Snow (Elsevier, 2024)
Introduction: Architectural characteristics of skeletal muscles are used to inform biomechanical analysis and candidacy for tendon transfer surgeries. Tendons of non-typical skeletal muscles may serve as optimal grafts, yet a thorough comparison of their parameters to those of typical musculature is not well represented in current literature. This study aims to analyze accessory extensor carpi radialis longus (aECRL) and accessory carpi radialis brevis (aECRB) muscles for their functional impact and suitability for use in tendon transfer surgeries. Methods: Out of 122 dissected forearms examined, one right aECRB and one left aECRL were discovered and photographed in situ. The accessory muscles, along with eleven other muscles associated with ECRL and ECRB tendon transfers from the same forearms, were analyzed for their sarcomere contraction states, structural properties, and maximal isometric force (Fmax) generating capacities. An architectural difference index was then calculated between each muscle to determine and discuss possible candidates for tendon transfer surgeries. Results: The Fmax of aECRL, ECRL, aECRB, and ECRB were determined to be 11.78 N, 57.24 N, 28.21 N, and 78.64 N, respectively. In this regard, aECRL and aECRB represented a 20.58% and 35.87% increase to ECRL and ECRB Fmax, respectively. The aECRL inserted with ECRB, and the aECRB inserted with ECRL. The aECRL and aECRB tendons, measuring 188.33 mm × 2.98 mm and 217.17 mm × 3.00 mm respectively, coursed independently with the ECRL and ECRB tendons to their shared insertions. The aECRL and aECRB muscles were each most structurally similar to the extensor pollicis longus and adductor pollicis muscles. Conclusions: Based on their morphology and structural characteristics, the aECRL and aECRB may be suitable grafts in adductorplasty or for extensor pollicis longus muscle/tendon repair. As the aECRL and aECRB tendons were relatively superficial and considerably long and wide, they may also be suitable for other musculotendon-based surgeries elsewhere in the body. This report may contribute new and beneficial insights for healthcare providers and medical educators when presented with cases where upper extremity musculotendinous reconstruction is warranted and/or non-typical musculoskeletal morphologies - particularly aECRL and aECRB - are present.